2001
DOI: 10.1099/0022-1317-82-8-2017
|View full text |Cite
|
Sign up to set email alerts
|

Cellular prion protein status in sheep: tissue-specific biochemical signatures

Abstract: Expression of the cellular prion protein PrPC is sine qua none for the development of transmissible spongiform encephalopathy and thus for the accumulation of the illness-associated conformer PrP Sc . Therefore, the tissue distribution of PrP C at the protein level in both quantitative and qualitative terms was investigated. PrP C was quantified using a two-site enzyme immunometric assay which was calibrated with purified ovine recombinant prion protein (rPrP). The most PrP C -rich tissue was the brain, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 42 publications
5
73
1
1
Order By: Relevance
“…Some suggested roles are reviewed [43] and include signal transduction, synaptic transmission, and protection against cell death. The prion protein is expressed in a wide variety of different organs, tissues and cells throughout the foetal and adult body and in cell lines [4,37,57,60,65,66,78].…”
Section: How Could Selection For Alleles Of the Prp Gene Influence Pementioning
confidence: 99%
“…Some suggested roles are reviewed [43] and include signal transduction, synaptic transmission, and protection against cell death. The prion protein is expressed in a wide variety of different organs, tissues and cells throughout the foetal and adult body and in cell lines [4,37,57,60,65,66,78].…”
Section: How Could Selection For Alleles Of the Prp Gene Influence Pementioning
confidence: 99%
“…Although only mammary gland samples of three sheep were analyzed, this finding indicates that PrP c expression in sheep may be quantitatively quite different from cattle. In ovine mammary glands, Moudjou et al (2001) found PrP c levels of up to 39 ng/g. Overall, within our study three different MAbs recognizing different epitopes of PrP and three different tests systems, with ELISA being the most sensitive method, were used.…”
Section: Resultsmentioning
confidence: 99%
“…Because it has been shown that conversion of PrP c to PrP sc plays a crucial role in prion disease (reviewed by Prusiner 1998), numerous investigations have addressed tissue-specific expression of PrP c in neurons and also in a variety of non-neuronal tissues of different species (Horiuchi et al 1995;Fournier et al 1998;Pammer et al 1999;Brown et al 2000;Ford et al 2000;Peters et al 2000;Burthem et al 2001;Moudjou et al 2001;Bounias and Purdey 2002;Tichopad et al 2003). With regard to the expression of PrP c in cattle, only few systematic investigations have been carried out so far.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the risk of PrP Sc accumulation in peripheral tissues, it is important to understand the distribution and expression levels of PrP c in these tissues. To date, although studies have been performed in rodents (15)(16)(17)(18), sheep (19,20), cervidae (21) and humans (22), PrP c levels in the peripheral tissues of cattle, which are regarded as transmission carriers of vcJd in humans, remain to be determined.…”
Section: Introductionmentioning
confidence: 99%